Srinaka Model: Development of Community Enterprise for an Inclusive Economy in Ban Na Subdistrict, Srinakarin District, Phatthalung Province, Thailand - Sampantamit, Tiptiwa; Aueaungkul, Apinan; Srichookiat, Sanit; Jansoon, Ninna; Kiriratinikom, Anut; Keawpibal, Naphat; Ngowsiri, Sutee; Odton, Wisan; Theppaya, Auttaphon; Salaebing, Muhammad; Intasaro, Kedsaraporn; Pinthongpan, Auttapong; et al. (Area Based Development Research Journal, 2025)
Background: Ban Na Subdistrict in Srinakarin District, Phatthalung Province in Southern Thailand, is endowed with abundant mountain forest resources and rich biodiversity. However, the community has long faced multidimensional poverty. Key challenges include the lack of effective mechanisms to manage natural resources for economic value creation, dependence on high-risk monocultural agriculture vulnerable to seasonal price fluctuations, limited access to professional skill development and marketing channels, and inadequate economic and social risk management at the household level. Against this backdrop, the Srinaka Model was developed as a grassroots economy framework designed to transform local livelihoods. Its central aim was to establish the Srinaka Community Enterprise and transition toward an inclusive economy, thereby addressing poverty through community-driven economic mechanisms, enhancing local capacity, and improving the long-term quality of life for vulnerable groups. Methods and Processes: A total of 56 vulnerable community members in Ban Na Subdistrict participated in training workshops and enterprise-building activities. The Srinaka Community Enterprise emphasized shared value creation through collaboration among academic institutions, government agencies, the private sector, civil society, and public communication networks. Together, they promoted the production of eco-friendly, naturally dyed, printed fabric that reflects the community’s cultural identity while integrating scientific knowledge and technological innovation. The implementation process unfolded across nine key steps: (1) strengthening collaborative power through leader discussions, focus groups, and workshops; (2) learning to prepare dyes from local raw materials and identifying native plants suitable for natural dyeing; (3) mastering dye extraction and mold making using betel nut sheaths and wood-metal composites; (4) skill-building workshops on fabric design and identity-basedpattern creation; (5) developing market-ready products in nine categories such as batik fabric, scarves, hats, T-shirts, trousers, dresses, bags, and notebooks; (6) applying eco-friendly production principles of reduction, recycling, and reuse; (7) building market linkages with external stakeholders; (8) forming networks with agencies such as the Department of Industrial Promotion and Thaksin University; and (9) knowledge transfer through school workshops and community learning forums, where experienced members mentored new participants. Economic Impacts: As a result, the group achieved remarkable economic growth. Average monthly income rose from 1,478.83 Baht (≈USD 41.50) to 5,886.83 Baht (≈USD 165.20). The enterprise successfully developed niche-market products, including printed fabric panels, scarves, and handkerchiefs, and later diversified into shirts, hats, skirts, trousers, dresses, and bags. Production capacity also scaled up significantly, with the group able to produce up to 60 yards of printed fabric per week and at least 30 finished items weekly. This capacity expansion enabled continuous and reliable income generation. Importantly, Srinaka fabrics received national recognition, being awarded a 5-star rating under Thailand’s OTOP (One Tambon One Product) program. The fabrics showcased innovative natural dyeing using mangosteen twigs and leaves in combination with sator pods, mordanted with limewater, and printed with betel nut sheath molds bestowed by the Thai Royal Project. These achievements underscore the group’s ability to add cultural and economic value to local products while positioning itself competitively in domestic and international markets. The value chain transformation extended beyond production. Originally centered on simply dyeing and selling fabric, the enterprise diversified into experiential tourism activities such as DIY (Do-It-Yourself) workshops. Visitors actively participated in dyeing and printing processes, enriching their cultural experience as co-creators of value while generating higher service fees for the community. This tourism innovation not only increased income but also strengthened community branding and identity. The group’s financial outcomes demonstrate clear progress. In 2023, total monthly revenue was 10,715.33 Baht (≈USD 300.30), with costs of 9,236 Baht and a net profit of 1,478.83 Baht. By 2024, revenue had surged to 30,147.34 Baht (≈USD 844.30), with costs of 24,260.50 Baht and net profit of 5,886.83 Baht. Average monthly wages for community labor also increased nearly threefold, from 6,429.17 Baht (≈USD 180.20) to 18,088.42 Baht (≈USD 506.40), ensuring more equitable distribution of income within the community. Although production costs rose significantly, the effective management of resources and diversification of income sources demonstrated improved resilience and financial sustainability. Social and Enviromental Impacts: Beyond economics, the social impacts of the Srinaka Model were substantial. The initiative created opportunities for participation across age and gender groups: women and the elderly took key roles in material preparation, dyeing, ironing, and customer service, while youth and children contributed to raw material collection, often as family activities. This inclusivity enhanced intergenerational collaboration and distributed benefits widely. Partnerships with government bodies, local administrations, and universities facilitated social learning and knowledge co-creation, reinforcing the community’s role as a learning hub. Environmental sustainability was embedded throughout the process. By substituting chemical dyes with natural plant-based alternatives, the group reduced water contamination risks and production costs while revitalizing the use of indigenous plants with economic potential. Circular economy practices were applied by reusing materials and minimizing waste. The community also engaged in youth-focused activities, such as “STEAM BCG Mud-Yom Rom Mueang”, promoting environmental awareness and aligning the Srinaka Model with Thailand’s Bio-Circular-Green (BCG) Economy strategy and the United Nations Sustainable Development Goals (SDGs). Conclusion: The Srinaka Model represents a holistic and replicable framework for grassroots economy development. By integrating local wisdom with modern knowledge, fostering inclusive participation, and linking natural and cultural capital with market opportunities, the model transformed Ban Na Subdistrict into both a production and learning center. Its success demonstrates how rural communities can build sustainable livelihoods, strengthen resilience, and contribute to inclusive economic growth in Thailand.